Experimental investigation of Smith-Purcell radiation focusing by using the parabolic gratings; International Journal of Modern Physics A; Vol. 25, iss. 01 : supplementary issue - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Sukhikh L. G. Leonid Grigorievich; Popov Yu. A. Yuriy Anatolevich (2010, 2010)
The Smith–Purcell radiation generated by relativistic electrons has been studied experimentally. To investigate the posibility of radiation focusing in the pre-wave zone two types of concave gratings focusing radiation in azimuthal and polar planes have been used. Comparison of radiation characteristics of such gratings with the flat grating ones in the same conditions has showed that application of concave gratings may significantly increase coherent Smith–Purcell radiation spatial density.